Ultrasound screening at 11-14 weeks of pregnancy for diagnosis of placenta accreta in mothers with a history of cesarean section - Ladan Younesi; Zahra Karimi Dehkordi; Zeinab Safarpour Lima; Ghazaleh Amjad (PAGEPress Publications, 2018)
The aim of this study was to add ultrasonographic screening criteria for placenta accreta in patients with cesarean section history at 11-14 weeks of gestation in order to identify those with the high risk of placenta accreta. Consequently, using ultrasound follow-up and confirmation of diagnosis can reduce mortality and morbidity. Pregnant mothers who were referred for routine screening for ultrasonography at 11-14 weeks of gestation were enrolled in the study if they had a history of cesarean section. Of the 184 subjects who were included in the study, 23 of the low-risk groups were excluded from study for some reason such as miscarriage and a lack of required information on the time of delivery. Among the 152 subjects, 27 were classified in the high-risk group (17.7%) and 125 subjects in the low-risk group (82.3%). Only one case in the high risk group was identified in patients with placenta accreta by ultrasound and clinical diagnosis, which has undergone a cesarean section at the gestational age of 35 weeks. There was no relationship between placenta accreta and disease risk, placenta previa, cesarean section, maternal age, and gravidity. Therefore, placenta accreta screening using ultrasonography can identify high-risk individuals at week 14-11 and with subsequent follow-up for improving prenatal prognosis.